Massive Levemir (Long-Acting) Insulin Overdose: Case Report - Mamatha Oduru; Mahmood Ahmad (Case Reports in Medicine)
A 52-year-old insulin-dependant diabetic man presented to the Emergency Department 2 hours after a deliberate massive overdose of 2100 units of long-acting Levemir insulin and a large quantity of whisky. On initial assessment, his GCS was 3/15 and his capillary blood sugar was 2.6 mmol/L. The patient was given a 50 ml bolus of 50% dextrose, followed by intravenous infusions of both 5% and 10% dextrose. Despite the continuous infusions, he experienced 4 symptomatic hypoglycaemic episodes in the first 12 hours after admission. These were managed with oral glucose, IM glucagon, and further dextrose boluses. Blood electrolytes and pH were monitored throughout. Insulin overdoses are relatively common and often occur with an excess of other drugs or alcohol which can enhance its action. Overdoses can result in persistent hypoglycaemia, liver enzyme derangement, electrolyte abnormalities, and neurological damage. Overall mortality is 2.7% with prognosis poorest in patients who are admitted with decreased Glasgow Coma scale (GCS) 12 hours after overdose.